KOMBINASI PROGRESSIVE MUSCLE RELAXATION (PMR) DAN AFIRMASI POSITIF TERHADAP PENURUNAN KECEMASAN DAN NYERI PASIEN JANTUNG - Lestaluhu, Masdarany; Peristiowati, Yuly; Elliana, Agusta Dian (STIKES ADVAITA MEDIKA TABANAN, 2024)
Coronary heart disease is a major cause of death, morbidity and decreased quality of life in general. Heart attack patients often feel anxious, scared and depressed. Because almost all patients realize that the heart is an important organ and when it is damaged, their health is threatened. Anxiety and the emergence of a fear of death in patients with myocardial infarction can cause severe pain. The purpose of this study was to prove the effect of applying a combination of Progressive Muscle Relaxation (PMR) and positive affirmations on anxiety and pain intensity of heart patients at the Tk Hospital. II. Prof. Dr. J.A. Latumeten Ambon. The research design that will be used is a Quasi Experiment with the type of pretest-posttest control group design, namely where researchers will measure the effect of treatment or action on the intervention group by comparing the control group. The sampling technique used is Consecutive Sampling with a sample of 24 respondents. Data analysis techniques using Paired t-test and Independent t test. The results showed that of the 24 respondents studied, it showed a significance value of 0.000 < (α = 0.05), this means that there is a significant effect between the application of a combination of Progressive Muscle Relaxation (PMR) and positive affirmations on anxiety and pain intensity of cardiac patients in Tk Hospital. II. Prof. Dr. J.A. Latumeten Ambon. With the application of a combination of Progressive Muscle Relaxation (PMR) and positive affirmations, it can improve the quality of life of heart patients.